First dinosaur encyclopedia - Bingham; Caroline (London DK, 2016)
A delightful first reference book about dinosaurs for young paleontologists, this updated edition of First Dinosaur Encyclopedia takes readers on a journey to the prehistoric world of dinosaurs.